Recepcja myśli posthumanistycznej we współczesnym obiegu popularnym = Comprehension of the post-humanistic notion in contemporary popular circulation - Mazurkiewicz, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Crisis of the anthropocentric discourse, together with expansive development of digital data, caused a situation, where human was - paradoxically - no longer placed in the center of post-modern humanities consideration. Its place was taken by forms of nonhuman consciousness, among whose hybrid-beings and the ones who are an effect of cyborgism play an important role.
Keywords: posthumanizm; kultura popularna; technologia; cyborg; cyfryzacja rzeczywistości; technofilia; postczłowiek; posthumanism; popular culture; anthropocentric discourse; cyberpunk